PENDIDIKAN ISLAM DAN PERKEMBANGAN PSIKOLOGI GENDER PADA PENYANDANG DISABILITAS HAMBATAN PENDENGARAN - Solihin Solihin (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2018)
This paper describes Islamic education and the development of gender psychology in persons with hearing impairments. One aspect that supports the implementation of Islamic education is the aspect of psychology. Psychology studies can touch directly on the personality structure of students, so that it can facilitate the process of information transformation. The quality of one's gender intelligence depends on the process of growth and development psychologically. The religious and cultural values ​​that develop in society also influence the psychological maturity of each gender. Hearing barriers are part of a separate problem in Islamic Education. Understanding this psychological condition is an important thing that must be done by everyone, especially educators because it is related to the development of the soul of deaf children. Psychological classification of deaf children who have been exposed above can facilitate learning that is carried out by educators, partially and in the context of the true purpose of Islamic education.